(untitled) (Global Journal of Management and Business Research, 2020)
The aim of this paper is to analyze the effect of the availability of electrical energy on the productivity of industrials companies in Cameroon To achieve this we used firm-level cross-sectional data from the World Bank Enterprise Survey WBES for the year 2016 and a two-step econometric approach The first step estimates total factor productivity through the Cobb-Douglas production function and the second step uses the IV-2SLS estimation method to correct both sample selection and endogeneity issues The results show that poor availability of electrical power does not affect the productivity of Cameroonian industrial companies because of the continuity of the production during the interruptions of the electric energy made possible through the use of generators by the company managers In addition firm size access to credit and innovation are factors that improve the productivity of Cameroonian industrial companies The results suggest that self-generation of electric power is a short-term solution to poor power availability Therefore improving domestic electricity generation would be important for improving industrial productivity growth of firms